Design of 2×250kN large-span hoist hydraulic automatic grabbing beam. Issue 1 (1st May 2022) - Cheng, Tanghua; Ren, Tao; Chai, Xu; Yao, Kun; Jia, Jiangming
Abstract: In water conservancy projects, automatic grabbing beams, as an important supporting equipment of mobile hoisting equipment, are widely used to improve the performance of operating gates and trash racks. This paper takes the hydraulic automatic grabbing beam of the 2 × 250kN large-span hoist at Baihetan Hydropower Station as an example. The design of the hydraulic automatic grabbing beam for the hoist is systematically analyzed, combined with engineering examples, and the most unfavorable conditions are used. As a result of the calculation, some design parameters of the long-span grab beam were obtained. The test results show that all performance indicators can meet the design requirements and relevant standard requirements.